ASEAN HUMAN RIGHTS DECLARATION: A NEW FORM OF UNIVERSALISM - Rachminawati, Rachminawati Rachminawati (UI Scholars Hub, 2014)
Just Recently ASEAN has adopted The ASEAN Human Rights Declaration. This declaration is a corner stone for ASEAN to establish human rights law instruments and mechanism in the future in order to support the upcoming ASEAN Community in 2015. However there are a lot of critiques upon the Declaration mostly come from human rights activist and NGOs. It is crticized that the declaration's principles and articles could be erode universality of human rights as stated in the Universal Declaration of Human Rights. Highly criticized is to article 7 of the Declaration which mention that the realization of human rights must be considered in the regional and national context bearing in mind differentpolitical, economic, legal, social, cultural, historical and religious backgrounds. It argues that this article will use as a tool for state to limit the people rights. Contrary to mainstream critiques, the paper argues that the declaration did not contain any principles that erode the universality of human rights and fundamental freedom. Article 7 of the declaration is a limitation of rights pursuant to the international human rights law called Margin of Appreciation. The margin of appreciation doctrine allows the court to take into effect the fact that the Convention will be interpreted differently in different member states. Judges are obliged to take into account the cultural, historic and philosophical differences between Strasbourg and the nation in question.